Energy dissipation in rocking bridge piers under free vibration tests. - Cheng, Chin-Tung (Earthquake engineering & structural dynamics.)
This research aims to investigate the dynamic characteristic of rocking bridge columns subjected to quick release loads. Precast columns anchored by unbonded steel bars at the centre of each column can rock on the foundation surface without inducing any residual deformation after earthquakes. The restoring force of columns relies on gravity load from the superstructure and tensile strength in anchor bars. Radiation damping is evaluated through each impact of column rocking. To validate the theoretical damping proposed by previous researchers, four columns were constructed. Research parameters included steel or plastic materials used as rocking interfaces, area of anchor bars, aspect ratio and size effect of columns. Test results revealed that stocky columns slid apparently in the first impact then rocked, but taller columns rocked with minor slips in the entire motion. And freestanding columns slid significantly in the first impact that led to a higher damping. Radiation damping due to impact in the entire motion for all tests was within 5%.